Institutional strategies to prevent violence in nursing work: an integrative review - Pereira, Cicera Adriana Rodrigues; Borgato, Maria Helena [UNESP]; Colichi, Rosana Maria Barreto [UNESP]; Bocchi, Silvia Cristina Mangini [UNESP] (Assoc Brasileira Enfermagem, 2019)
Objective: To analyze the production of research that adopted as object of investigation: institutional strategies, actions and programs to curb and/or prevent the nursing workplace violence. Method: Integrative review of 14 articles in full, available in the databases LILACS, PubMed Central, Scopus, CINAHL and Web of Science. Results: Of the articles analyzed, most arise from quantitative research (71%), carried out in the United States (65%), with educational actions (57%) and programs (43%), denoting policies. Conclusion: Results showed various ways to curb or prevent nursing workplace violence. These are specific strategies, there are few programs deployed worldwide, usually centered in the United States, Canada and Sweden. Most of them is well evaluated and can serve as a model for the development and dissemination of policies according to the needs of each location.
Keywords: Occupational Health; Violence; Work; Nursing; Programs